2012
DOI: 10.1177/1524839912457567
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Correct Car Seat Use in Parents of Young Children

Abstract: Injuries involving motor vehicles continue to be the biggest threat to the safety of children. Although child safety seats (CSS) have been established as a central countermeasure in decreasing injury risk, the majority of parents do not use the correct car seat correctly. There are many challenges in promoting correct car seat use, which itself is a complex behavior. To advance this critical protective behavior, the public health community would benefit from clarifying CSS messaging, communicating clearly, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…Technology is advancing in CRSs, as well as vehicles, but parents and caregiver need to utilize the CRS in order to keep their child safe. To support parents and caregivers in using the appropriate CRSs for their child on every ride, interventions and public health campaigns may need be targeted and have clear messages to address those in which parents may be more willing to not fully buckle their child [ 27 , 28 ]. For example, we saw that for the taxi and car sharing service situation, 23.6% and 13.1% of booster seat and car seat users, respectively, agreed or somewhat agreed they would not fully buckle their child.…”
Section: Discussionmentioning
confidence: 99%
“…Technology is advancing in CRSs, as well as vehicles, but parents and caregiver need to utilize the CRS in order to keep their child safe. To support parents and caregivers in using the appropriate CRSs for their child on every ride, interventions and public health campaigns may need be targeted and have clear messages to address those in which parents may be more willing to not fully buckle their child [ 27 , 28 ]. For example, we saw that for the taxi and car sharing service situation, 23.6% and 13.1% of booster seat and car seat users, respectively, agreed or somewhat agreed they would not fully buckle their child.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline results identified common critical CRS misuse. [25][26][27][28] Even though participants were instructed to install their CRS based on CRS and motor vehicle instructions, we observed that instructions and knowledge were not sufficient to provide the complex skills necessary to properly install and use a CRS. 29 30 We determined that BST procedures provided participants with the hands-on critical skills needed for correct CRS installation and use.…”
Section: Discussionmentioning
confidence: 99%
“…Digital signage technology (DST) is a contemporary approach to health messaging that uses flat-panel monitors to display “media rich” messages 12 in “dwell zones.” Proposed as a solution to address the short shelf-life of printed materials and the limited interaction time of health care providers 13,14 I selected DST as the best medium for delivering the intervention message. Radon program bulletin boards and hand cards, defined as the standard of care, were available in both the pre- and postintervention phases at all sites.…”
Section: Methodsmentioning
confidence: 99%